Are the clinical features of leprosy and American tegumentary leishmaniasis worse in patients with both diseases? - Carvalho, Amanda Gabriela de (2022)
This cross-sectional population-based study compared clinical features of leprosy and American tegumentary leishmaniasis (ATL) in patients diagnosed with both diseases (n=414) and in those diagnosed with only leprosy (n=27,790) or only ATL (n=24,357) in Mato Grosso State, which is a hyperendemic area for both diseases in Midwest Brazil. All new cases of leprosy and ATL reported in the area from 2008 to 2017 were included. Patients diagnosed with both diseases were identified by a probabilistic linkage procedure applied to leprosy and ATL databases of the national reporting system. The distribution of the frequency of clinical features between groups was compared by the chi-square test, followed by a multivariate logistic regression. Patients diagnosed with both leprosy and ATL presented higher odds of having nerve damage (OR: 1.34; 95% CI: 1.09–1.66) and leprosy reactions (OR: 1.35; 95% CI: 1.04–1.76) compared to patients diagnosed only with leprosy. Mucocutaneous leishmaniasis (OR: 2.29; 95% CI: 1.74–3.00) was more frequent among patients with both diagnoses when compared to patients who only had ATL. In conclusion, patients diagnosed with both leprosy and ATL present more severe clinical features of such diseases. Our data can be useful for designing health policies aimed at timely and integrated management of leprosy and ATL in co-endemic areas.